A comparative study reveals the key biological traits causing bioinvasion differences among four alien species of genus Veronica in China. (15th June 2022) - Liu, Yujing; Wu, Hairong; Wang, Congyan; Cheng, Jiliang; Qiang, Sheng
Abstract: The four alien farmland weeds of genus Veronica (i.e. V. arvensis, V. didyma, V. hederifolia and V. persica ) have successfully colonized in China, but caused different ecological consequences in the colonized habitats. However, the key biological traits conferring bioinvasion differences under different light conditions among the four alien species of Veronica remain unknown. A comprehensive contrastive analysis experiment was conducted to assess the contribution of the intensity of photosynthetic and sexual and asexual reproductive traits of the four alien Veronica weeds to their invasion level in both field trial and laboratory. The field survey showed that V. persica had the highest invasion level, followed by V. didyma, V. hederifolia and V. arvensis . Their invasiveness was mainly attributed to photosynthetic-related parameters (LMA) and asexual reproduction traits (the ratio of adventitious roots) out of all the 22 tested indexes. The photosynthetic-related and some asexual reproduction indexes from separate determinations under both sun and shade conditions showed that V. persica was able to adapt to strong illumination but was more tolerant of shade than the other species. This adaptive differentiation to illumination conferred different competitiveness over crops on the four alien Veronica weeds by allocating resources to the biomass of each organ in farmland. It may be concluded that the adaptability to illumination conditions and the asexual reproduction traits may endow their successful invasion and become different important farmland weeds.